ANALISIS INFORMASI PESERTA DIDIK PADA PENGGUNAAN MOBILE LEARNING BASED ON SOCIAL MEDIA MENGGUNAKAN METODE DATA MINING - Yanuar Sinatra; Rahman Arifuddin (Sinteks : Jurnal Teknik, 2018)
This study aims to analyze the information data of students based on the similarity ofattributes using data mining methods. The method used in this study is the J.48 Classifierclassification technique on WEKA data mining and Orange data mining software. This study showsthat data mining can be used as an alternative method to see the relationship between a variable orclass from the attributes of students who use mobile learning applications. This study found that theknowledge of mobile learning did not determine the results of the pretest, but indirectly determinedby the level of self-efficacy possessed by students. Data mining methods can be implemented tomeasure the correlation between classes or variables in research.